Rancang Bangun Inverter DC Ke AC Satu Fasa Mode Push Pull Berbasis Arduino - Supriyanto, Anang (2016)
Inverter is one of the electronic devices that used to changing the voltage from DC (Direct Curent) into voltage AC (Alternating Curent). The output from inverter can be an AC voltage with the form of sine wave, square wave, and sine wave modification. This inverter serves as a provider of backup power, either in a vehicle or at home, as emergency power when the electricity die out home. Furthermore, a DC to AC inverter will play an important role in changing the DC energy from renewable energy sources such as solar cells became AC electrical energy that used daily. The design of DC to AC inverter of this phase using a push pull inverter type, where the arduino module as frequency wave generator that will generate a frequency of 50Hz, and the center-tap transformer as a step-up voltage. The actual results of the design is the frequency generated by the inverter approached sine with a frequency generated at 55Hz, and the voltage generated when no load with source 7ah 12v battery 215 vac and the current generated of 1 ampere, the results of the testing able to turn on 10 watt lamp as a load, 10 watt fan, and 40 watt solder, maximum power that generated bby the inverter is 50watt.